SOSIALISASI PENGEMBANGAN PERTANIAN LAHAN KERING DAN PEMANFAATAN AIR TANAH DALAM DI DESA SALUT KECAMATAN KAYANGAN, KABUPATEN LOMBOK UTARA - I Dewa Gede Jaya Negara; Bambang Hari Kusumo; Kisman Kisman; Tajidan Tajidan; Lolita Endang Susilawati; Bambang Budi Santoso; Joko Priyono (Jurnal Abdi Insani, 2022)
The potential for dry land in North Lombok is very wide with the surrounding rivers mostly dry during the dry season. Sambik Rindang Hamlet is one of the dry lands that has the potential for productive agriculture, but has not been able to be utilized optimally. For this reason, the people of Sambik Rindang need to be given knowledge about this through socialization, so that they can make efficient use of dry land and groundwater so that farming can be carried out outside the rainy season. The aim of the socialization is to increase people's knowledge about irrigation water efficiency and irrigation methods for agriculture in dry land. This socialization was carried out with the stages of field review, field socialization, discussion and question and answer, evaluation and closing. Furthermore, this socialization service has succeeded in providing knowledge about efficient irrigation such as drip irrigation and pipelines, with productive farming. The service participants were very enthusiastic about participating in the socialization activities, questions about agriculture and irrigation were answered well by the team from the Faculty of Agriculture and the Faculty of Engineering. Evaluation of activities is carried out by the service team, from the field socialization activities to the end of the activity. The service participants were very proactive during the activity and had knowledge about efficient irrigation and productive farming methods. Thus the service participants have known efficient irrigation methods and have gained knowledge in utilizing dry land in order to have an economic impact on the family.